Formulasi Kukis yang Diperkaya Antioksidan dan Serat dengan Kulit Buah Naga Merah dan Tepung Tempe sebagai Camilan Fungsional bagi Penderita Diabetes: Formulation of Antioxidant and Fiber Enriched Cookies with Red Dragon Fruit Peel and Tempeh Flour as A Functional Snack for Diabetics - Tutik Ernawati; Wiwi Febriani; Ramadhana Komala; Dian Isti Angraini; Sofyan Musyabiq Wijaya; Andi Eka Yunianto (Amerta Nutrition, 2025)
ackground: Antioxidants and dietary fiber are important to human health as well as the prevention of diabetes. Red dragon fruit peel has a high content of anthocyanins and fibre, while tempeh flour contains plant proteins, as well as bioactive compounds such as soy isoflavones, which are capable of even boosting the antioxidant activity. Glypide , being a P-gp inhibitor, the addition of glibenclamide will have the potential to develop a functional food product for treatment and/or management of diabetes. Objectives: This study aims to analyze the antioxidant and fiber of cookies from red dragon fruit peel flour and tempeh dumpling flour as functional snack for diabetes mellitus patients. Methods: This experimental investigation adopted the Completely Randomized Design (CRD) with four levels of wheat flour substitution: F0 (100:0), F1 (90:10), F2 (75:25) and F3 (50:50). Chemical composition included dietary fiber (enzymatic-gravimetric method) and antioxidant capacity as vitamin C (HPLC-PDA), total carotenoids, flavonoids, phenols, tannins and DPPH antiradical power methods (spectrophotometry). Comparisons were tested by one-way ANOVA (α=0.05). Results: Red dragon fruit peel flour was substituted, which resulted in a significant increase in dietary fiber and antioxidant content (p-value<0.05). When compared to other formulas, Formula F3 showed the highest levels of total phenols (362 mg GAE/100 g), flavonoids (14.77 mg), antioxidant activity (69.2%), and dietary fiber (30.87%) (p-value<0.05). As more red dragon fruit peel flour was substituted, vitamin C and carotenoid levels also rose. Conclusions: Because of their high dietary fiber and antioxidant content, formula F3 cookies may be a useful snack for people with diabetes.